EFFECTS OF EXPLANT TYPE, CULTURE MEDIA AND PICLORAM AND DICAMBA GROWTH REGULATORS ON INDUCTION AND PROLIFERATION OF SOMATIC EMBRYOS IN EUCALYPTUS GRANDIS X E. UROPHYLLA1 - Moura,Luciana Coelho de (2017)
ABSTRACT The objective of the present study was to test the effects of explant type, auxin concentrations, culture media, and auxin concentrations on the induction and proliferation of somatic embryos of Eucalyptus grandis x E. urophylla. Seeds and cotyledons were used as explants and inoculated in culture media containing 1.13, 2.26, 3.39 and 4.52 µM dicamba or 4.14, 10.35, 20.71 and 31.06 µM picloram. Embryogenic calli induced in the picloram treatments were used as explants and inoculated in semisolid or liquid media containing 4.14, 10.35, 20.71 and 31.06 µM picloram and keeping the origin of the embryogenic callus (seeds or cotyledons) and the concentration of picloram in those who were in the induction phase. Statistical, descriptive and anatomical analyses were performed. Induction of somatic pro-embryos into the juvenile plant material of Eucalyptus grandis x E. urophylla was performed using seeds or cotyledons as the source of explants, with the addition of dicamba and picloram as growth regulators. The use of cotyledons as a source of explants and the concentration of 4.1 µM picloram added to the culture media resulted in a higher induction of somatic pro-embryos. Proliferation of secondary somatic embryos was achieved using liquid medium added with picloram.